1995
DOI: 10.1111/j.1346-8138.1995.tb03354.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Chemotherapy‐induced Acral Erythema

Abstract: Three cases of chemotherapy-induced acral erythema are reported. All the patients had received cyclophosphamide, vincristine, adriamycin, prednisolone, and granulocyte-colony stimulating factor (G-CSF) for the treatment of leukemia or malignant lymphoma. From 35 to 45 days after the start of chemotherapy, painful erythematous lesions developed on their palms, soles, fingers, and toes, resulting in blister formation and desquamation. The recent higher incidence of chemotherapy-induced acral erythema may be corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A regular application of topical petroleum-lanolin ointment base with hydroxyquinolone sulphate three times per day was rendered effective, also reported by Chin et al (2001). Topical corticosteroids have an effective role in the management of symptoms however these may also cause thinning of the skin (Komamura et al, 1995;Vakalis et al, 1998), which was observed in some female patients in our study. The patients were also prescribed with Vitamin B6, which is known to be highly effective in both the prophylaxis and control of symptoms (Fabian et al, 1990).…”
Section: Discussionmentioning
confidence: 71%
“…A regular application of topical petroleum-lanolin ointment base with hydroxyquinolone sulphate three times per day was rendered effective, also reported by Chin et al (2001). Topical corticosteroids have an effective role in the management of symptoms however these may also cause thinning of the skin (Komamura et al, 1995;Vakalis et al, 1998), which was observed in some female patients in our study. The patients were also prescribed with Vitamin B6, which is known to be highly effective in both the prophylaxis and control of symptoms (Fabian et al, 1990).…”
Section: Discussionmentioning
confidence: 71%
“…It is important to make patients with CIAE aware of the natural course in order to prevent them from becoming overly anxious (8). CIAE, especially erythrodysesthesia, is usually so painful that it requires treatment such as systemic or topical steroids (5, 6, 9), elevation of the legs (8), and application of cold compression to the lesion (5, 9). Treatment with steroid ointment using ODT was effective and prophylactic for the ertyhrodysesthesia in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, topical corticosteroids have been useful for the prophylaxis and treatment of HFS. However, that treatment in capecitabine-associated HFS up to date is not proven [6]. Although its efficacy has not been proven in clinical studies, certain authors report on the use of prophylactic or therapeutic pyridoxine supplementation for the prevention or minimisation HFS lesions [7].…”
Section: Introductionmentioning
confidence: 99%